Unresolved issues in risk communication research: the case of the H1N1 pandemic (2009–2011). (27th August 2013) - Barrelet, Clara; Bourrier, Mathilde; Burton‐Jeangros, Claudine; Schindler, Mélinée
Abstract : The 2009 H1N1 pandemic had considerable impact on risk perceptions, vaccination campaigns, and global health governance. In this context, risk communication issues have been probably the most puzzling and the least understood in retrospect. This article reviews the current knowledge on the following issues: risk and pandemic perceptions; vaccination perceptions and practices; rumors and rumor propagation; and health risk communication. It also highlights the research gaps in these areas that remain to be further explored in the future.